Radiated seismic energy from coda measurements and no scaling in apparent stress with seismic moment (2010)
The seismic coda consists of scattered waves that leave the earthquake source in a variety of directions. The averaging of source radiation that results leads to stable ground motion spectra that we use as the basis for a robust measurement of radiated wave energy. We apply an empirical Green's function (EGF) method to the seismic coda in order to investigate scaling of the radiated seismic energy. We correct for path effects in the spectra of earthquakes by using a stack of closely located, small earthquakes as an EGF. We apply this approach to four earthquake sequences in western North America that span a magnitude range from M w 3.0–M w 7.1. Our estimates of scaled energy are consistent with independent measurements, where available. We find no dependence in individual seismic energy estimates on source?station distance, which validates the EGF approximation. We find that a constant scaled energy of 3.5 × 10?5 provides a reasonable fit to the data, with no dependence of the scaled energy on seismic moment.